Feasibility of Using Baghouse Dust from Asphalt Plants as Partial Replacement of OPC in M20 Concrete (OODBODHAN, 2026)
Concrete production heavily relies on ordinary Portland cement (OPC), which significantly contributes to global CO₂ emissions and raises construction costs. Reusing industrial byproducts becomes an important step toward sustainability. However, the potential of baghouse dust (BHD) from asphalt plants as a cement substitute remains largely unexplored in Nepal, creating the need to assess whether this plentiful waste material can partially replace cement without compromising concrete quality. This study examined the feasibility of using BHD from an asphalt plant in the Pokhara Valley as a partial replacement for OPC in M20 concrete, with BHD used at 0%, 5%, 10%, and 15% replacement levels, while maintaining a water-to-cement ratio of 0.40. The study evaluated the properties of fresh concrete, including slump and bulk density, as well as the hardened properties of compressive, split tensile, and flexural strengths at both 7 and 28 days. Water absorption tests were also performed at 28 days to assess permeability. Results indicated that the slump slightly decreased as the BHD content increased, while the bulk density dropped by about 2–2.5% at a 15% replacement, reflecting minor changes in workability and particle packing. Mechanical testing revealed that a 5% BHD replacement yielded the best performance, improving strength at both ages. In contrast, higher dosages (10–15%) reduced strength due to binder dilution and increased micro-voids. Water absorption marginally increased at 5–10% replacement due to finer particle packing and micro-pore refinement, indicating a denser microstructure, but increased at 15%, likely due to higher porosity. Overall, the findings suggest that BHD can be effectively reused as a low-level (5–10%) cement replacement to improve strength and durability in non-structural and moderately loaded concrete applications, provided the source quality and long-term behavior are properly evaluated.